Identification of β-hydroxybutyrate as a potential biomarker for female papillary thyroid cancer. (20th March 2019) - Chen, Jian; Hou, Hongwei; Chen, Huan; Luo, Yanbo; He, Yunlu; Zhang, Lirong; Zhang, Yunfei; Liu, Hansong; Zhang, Fangfang; Liu, Yong; Wang, An; Hu, Qingyuan
Aim: β-Hydroxybutyrate (BHB) was proved to be a differential metabolite of papillary thyroid cancer (PTC) by semiquantitative analysis, while whether BHB could be used as a potential biomarker for female PTC still needed to be validated.Materials & methods: An LC–MS/MS method with surrogate matrix was established to validate serum BHB in specified PTC patients.Conclusion: Serum BHB levels in PTCs were significantly higher than those in HCs. For both serum BHB with a cut-off value of 312.5 ng/ml and serum BHB/creatinine of 33.5 μmol/mmol, a promising prediction rate to distinguish low-grade PTCs from HCs with satisfactory sensitivity and specificity was achieved,  indicating that serum BHB might be proved as a useful biomarker for low-grade female PTC.